Layered Ruddlesden–Popper Efficient Perovskite Solar Cells with Controlled Quantum and Dielectric Confinement Introduced via Doping. (27th May 2019) - Li, Hao; Wang, Xikui; Zhang, Tao; Gong, Xiu; Sun, Qiang; Pan, Han; Shen, Yan; Ahmad, Shahzada; Wang, Mingkui
Abstract: Layered Ruddlesden–Popper (RP) hybrid perovskite semiconductors have recently emerged as promising materials for photovoltaics application. However, the strong quantum and dielectric confinement of RP perovskite compounds increases their optical bandgap and binding energy of exciton, which limit their application in solar cells. Herein, the doping of RP‐based (BA)2 (MA)3 Pb4 I13 perovskite materials by means of Li + is reported for the first time, which can significantly help to reduce dielectric confinement and thus the exciton‐binding energy via reducing the dielectric constant difference between organic spacer cation and inorganic framework. Furthermore, the Li + doping boosts the carrier mobility, reduces the trap density states, and thus allows to achieve power conversion efficiency of ≈15% via Li + ‐(BA)2 (MA)3 Pb4 I13 ‐based perovskite solar cell, which is the highest efficiency for layered perovskites ( n = 4) so far. This work highlights the promising ionic doping engineering for further improvement of the layered perovskite materials. Abstract : Li + doping layered Ruddlesden–Popper (RP) hybrid perovskite RP (BA)2 (MA)3 Pb4I13 perovskite can significantly help to reduce dielectric confinement and thus the exciton‐binding energy. The Li + ‐doped RP perovskite film shows high carrier mobility, low trap density states, and achieves a power conversion efficiency close to 15%.